P162 CT follow up after surgery for lung cancer – should the availability of radio-surgery prompt a change in screening protocol to detect early intracerebral recurrence?. (12th November 2015) - Roberts, S; Jones, L; Exley, C
Abstract : Although routinely performed, the optimal screening regimen for recurrent disease after curative surgery for lung cancer has yet to be agreed. Radio-surgery has improved prognosis for patients with limited intra-cerebral metastases, 1 however screening for intracerebral recurrence has little evidence base. Local protocol is to perform CT head/chest/abdomen pre surgery and CT chest/abdomen at 3, 12 and 24 months after surgery. We proposed that the addition of CT head to the post-surgical protocol would enable earlier detection of intra-cerebral recurrence, facilitating timely treatment. CT head was added to standard post surgical surveillance programme in February 2015. CT reports were reviewed prospectively and we report data to June 2015. For comparison, retrospective data for all patients currently enrolled in screening was also reviewed. All 222 CT scans for the 115 patients undergoing post-surgical surveillance were reviewed. 28 of these have been performed since our protocol changed to include CT head. In total, 22 patients (19%) had recurrent disease. 2 patients had isolated intracerebral recurrence. This represents 9% of all patients with recurrent disease and these patients would not be identified on previous screening protocol. This is in line with findings from previous work. 2 Four cases of symptomatic intra-cerebral recurrence were identified prior to protocol change. Only one of these patients was eligible for radio-surgery. Since protocol change, one case of asymptomatic isolated intra-cerebral recurrence has been detected through screening; this patient was thereafter treated with radio-surgery. Our results show that isolated intra-cerebral recurrence would be missed on the previous screening protocol. These preliminary results suggest that the addition of CT head in post operative surveillance enables earlier identification of these patients. The earlier detection of intracerebral recurrence as a result of screening may increase referrals for radio-surgery, with potential for improved survival. References: 1 Andrews, et al . Lancet 2004;363 :1665 2 Yokoi, et al . Ann Thorac Surg . 1996;61 :546